The Effect of Supply Chain Quality Integration on Supply Chain Management Practice to Achieve Supply Chain Performance - Monika Kussetya Ciptani; Yunica Wahyu Dewantari (JAAF (Journal of Applied Accounting and Finance), 2019)
In manufacturing company, quality of product could become their competitive advantage to compete in the market. To achieve good quality of products and activities, company need to have system or strategy to manage their supply chain activity and make it more effective and efficient flow of production and improve the quality of information sharing, production time, and products, so the company can improve their performance. This study conducted to find out the mediating effect of supply chain quality integration on supply chain management practices to achieve performance. Researcher was using PLS Structural Equation Modelling (PLS-SEM) to analyze data. The sample of this research was consumer goods manufacturing in Indonesia and using primary data with questionnaire as data collection method. After analysis using PLS-SEM, researcher was found that supply chain management practices affect operational performance; and supply chain quality integration has mediating effect on the effect of supply chain management practices on operational performance of company.